Economics without Borders Economic Research for European Policy Challenges - Matyas, Laszlo; Blundell, Richard; Cantillon, Estelle; Chizzolini, Barbara; Ivaldi, Marc; Leininger, Wolfgang; Marimon, Ramon; Steen, Frode (Social Sciences, 2017)
This book, with contributions from leading European economists, uses state-of-the-art surveys to bridge the gap between economics research and policymaking in Europe, demonstrating how recent research is contributing to European policy. Also available as open access, it is for economics scholars, economists and policymakers working in Europe.